PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS INKUIRI TERBIMBING PADA SUBTEMA KEBERAGAMAN MAKHLUK HIDUP DI LINGKUNGANKU - FITRIYANI, Atin (2014)
This research is the development of 4D models Thiagarajan. The products produced in this study is the Student Worksheet (LKS) based guided inquiry. According to Prastowo (2011, hlm. 201) states "LKS is a printed teaching materials in the form of sheets of paper containing material, summaries, and guidelines implementing the learning task to be done by learners, which refers to the basic competencies to be achieved ". Thus, LKS contains learning activities and provides a student-centered activity, also the teaching materials that can be developed by the teacher as a facilitator in the learning activities. The results of the expert validation showed that 95% of guided inquiry-based worksheets and practical declared invalid. 1 trial results mean better student learning outcomes are cognitive scores 3.66 on a scale of 1-4, psychomotor B value and the value apektif B. The response of students to the use of guided inquiry worksheets on trial 1 was positive with 97% of students rate the positive . The results of trial 2, the average student learning outcomes have increased the value of 4 on a scale of 1-4 cognitive, psychomotor value B+ and value apektif B. The response of students to the use of guided inquiry worksheets on trial 2 was positive with 98% of students rate the positive . The next stage is the dissemination of the results of both student learning and students' response to positive guided inquiry-based worksheets. Thus the terms validity, practicality and effectiveness can be met and guided inquiry-based worksheets subtema diversity of living things in a decent neighborhood used in class IV SDN Angkasa 1. Keywords: development, student worksheets, guided inquiry, subthemes diversity of living things in my neighborhood Penelitian ini merupakan penelitian pengembangan model 4D Thiagarajan. Produk yang dihasilkan dalam penelitian ini adalah Lembar Kerja Siswa (LKS) berbasis inkuiri terbimbing. Menurut Prastowo (2011, hlm. 201) menyatakan "LKS merupakan suatu bahan ajar cetak berupa lembar-lembar kertas yang berisi materi, ringkasan, dan petunjuk-petunjuk pelaksanaan tugas pembelajaran yang harus dikerjakan oleh peserta didik, yang mengacu pada kompetensi dasar yang harus dicapai".Dengan demikian, LKS berisi kegiatan pembelajaran dan menyediakan aktivitas yang berpusat pada siswa, juga merupakan bahan ajar yang dapat dikembangkan oleh guru sebagai fasilitator dalam kegiatan pembelajaran.Hasil dari validasi ahli menunjukan bahwa 95% LKS berbasis inkuiri terbimbing dinyatakan valid dan praktis. Hasil uji coba 1 rata-rata hasil belajar siswa baik yaitu nilai kognitif 3,66 pada skala 1-4, nilai psikomotor B dan nilai apektif B. Respon siswa terhadap penggunaan LKS inkuiri terbimbing pada uji coba 1 adalah positif dengan 97% siswa menilai positif. Hasil uji coba 2, rata-rata hasil belajar siswa mengalami peningkatan yaitu nilai kognitif 4 pada skala 1-4, nilai psikomotor B+ dan nilai apektif B. Respon siswa terhadap penggunaan LKS inkuiri terbimbing pada uji coba 2 adalah positif dengan 98% siswa menilai positif. Tahap selanjutnya adalah penyebaran dengan hasil belajar siswa baik dan respon siswa terhadap LKS berbasis inkuiri terbimbing positif. Dengan demikian syarat kevalidan, kepraktisan dan keefektipan dapat terpenuhi dan LKS berbasis inkuiri terbimbing subtema keberagaman makhluk hidup dilingkunganku layak digunakan di kelas IV SDN Angkasa 1. Kata Kunci : pengembangan, lembar kerja siswa, inkuiri terbimbing, subtema keberagaman makhluk hidup di lingkunganku